Next-generation sequencing analysis of endometrial screening liquid-based cytology specimens: a comparative study to tissue specimens - Toshiaki Akahane; Ikumi Kitazono; Shintaro Yanazume; Masaki Kamio; Shinichi Togami; Ippei Sakamoto; Sachio Nohara; Seiya Yokoyama; Hiroaki Kobayashi; Tsubasa Hiraki; Shinsuke Suzuki; Shinichi Ueno; et al. (BMC, 2020)
Abstract Background Liquid-based cytology (LBC) is now a widely used method for cytologic screening and cancer diagnosis. Since the cells are fixed with alcohol-based fixatives, and the specimens are stored in a liquid condition, LBC specimens are suitable for genetic analyses. Methods Here, we established a small cancer gene panel, including 60 genes and 17 microsatellite markers for next-generation sequencing, and applied to residual LBC specimens obtained by endometrial cancer screening to compare with corresponding formalin-fixed paraffin-embedded (FFPE) tissues. Results A total of 49 FFPE and LBC specimens (n = 24) were analyzed, revealing characteristic mutations for endometrial cancer, including PTEN, CTNNB1, PIK3CA, and PIK3R1 mutations. Eight cases had higher scores for both tumor mutation burden (TMB) and microsatellite instability (MSI), which agree with defective mismatch repair (MMR) protein expression. Paired endometrial LBC, and biopsied and/or resected FFPE tissues from 7 cases, presented almost identical mutations, TMB, and MSI profiles in all cases. Conclusion These findings demonstrate that our ad hoc cancer gene panel enabled the detection of therapeutically actionable gene mutations in endometrial LBC and FFPE specimens. Endometrial cancer LBC specimens offer an alternative and affordable source of molecular testing materials.